2012
DOI: 10.1007/s10457-012-9492-x
|View full text |Cite
|
Sign up to set email alerts
|

Root system of Quercus suber L. seedlings in response to herbaceous competition and different watering and fertilisation regimes

Abstract: Different management practices are commonly applied to increase pasture yield of Mediterranean open woodlands, but the consequences of increasing competition for soil resources with these practices on tree recruitment are still unknown. In a greenhouse study, belowground competition of Quercus suber L. seedlings growing together with natural (Oak NP ) or improved pasture (Oak IP ) was evaluated, and their root systems compared with those of seedlings growing in bare soil (Oak BS ). Two watering levels and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…This strategy underlines the importance of root development to explore a larger volume of soil, as reported in other species of oaks (Cubera, Moreno, Solla, & Madeira, 2012). On the other hand, no significant changes were made in root biomass under different treatments.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This strategy underlines the importance of root development to explore a larger volume of soil, as reported in other species of oaks (Cubera, Moreno, Solla, & Madeira, 2012). On the other hand, no significant changes were made in root biomass under different treatments.…”
Section: Discussionsupporting
confidence: 64%
“…It seems that the seedlings used their limited reserves of carbon to develop roots. This strategy underlines the importance of root development to explore a larger volume of soil, as reported in other species of oaks (Cubera, Moreno, Solla, & Madeira, 2012).…”
Section: Discussionmentioning
confidence: 61%
“…According to Jones et al (1997), early emergence can lead to higher survival and biomass accumulation, as well as provide a competitive advantage compared with seedlings that emerge later. Other researchers (Cubera et al, 2012;Gordon, Welker, Menke, & Rice, 1989;Rey-Benayas, Navarro, Espigare, Nicolau, & Zavala, 2005) have shown that, in the Mediterranean climate, summer drought is the main factor limiting water availability, and competition for soil water by herbaceous plants is an additional cause of water limitation for oak seedlings. ORCID Barbara Mariotti http://orcid.org/0000-0003-3779-2104…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased pasture growth could reinforce competition for soil resources, with negative consequences for young seedlings (Cubera et al. ). In contrast, Cistus arrests pasture growth (Rivest et al.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of Retama on the production of pasture understorey (Pugnaire et al 1996;Rodríguez-Echeverría & Pérez-Fernández 2003;Armas et al 2011;Rivest et al 2011) suggests that this shrub could attract herbivores and thus may lead to higher losses through browsers once seedlings are established. In addition, increased pasture growth could reinforce competition for soil resources, with negative consequences for young seedlings (Cubera et al 2012). In contrast, Cistus arrests pasture growth (Rivest et al 2011) and herbivores may be attracted to a lesser extent.…”
Section: Specific Combinations Of Shrub Species and Life Stages Can Imentioning
confidence: 99%